IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PENGELOLAAN SAMPAH DI KELURAHAN EMPAGAE KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Asyurah, Muh. Aswan; Sapri; Ibrahim, Monalisa (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the implementation of government policy on waste management in Empagae Village, Watang Sidenreng District, Sidenreng Rappang Regency. The method used in this research is the regression correlation method with a quantitative approach. The population in this study was the entire family card (KK) 934 Family Cards, while the sample taken was 82 people. The data collection technique used is distributing questionnaires and documentation. Data processing uses the Statistical Product and Service Solutions (SPSS 21) application.Based on the results of policy implementation research, 70% of the results of the recapitulation of waste management indicators, the highest is Reduce (reducing) by 71%, and the lowest is Reuse (reuse) and Reduce (recycling) with the same results of 67% results or total frequency of answers the highest weight is 68%. And the results of the recapitulation of factors that influence variable ideal yield 65%. In the one sample test table it shows a statistical value of 2,851 with a regression coefficient table of 0.597 so that the calculated t table value of the government policy implementation variable is 469,289 or 469,298>1662, so Ho is rejected and Ha is accepted, meaning it is significant, so the implementation of government policy on waste management has a positive effect and significant.